IMPLEMENTATION OF THE SMART CITY PROGRAM TO IMPROVE PUBLIC SERVICES IN SEMARANG CITY - Wahyuni, Herpita; Purwaningsih, Titin; Herlina, Nia (Universitas Negeri Yogyakarta, 2021)
This study aims to determine the implementation of Semarang Smart City in improving public services. This study uses qualitative research methods sourced from various literature or literature studies in answering the research results. The findings found that Smart living with free WIFI service, an ambulance is available 24 hours a day. Smart living is responsive to various community reports, such as reports on water pumps that don't flow. Bright Environment successfully manages a harmonious, comfortable, and clean Environment by turning a slum village into a healthier and cleaner city. Smart mobility with the Bus Rapid Transit (BRT) service aims to provide an alternative mode of transportation that is reliable and safe for the citizens of Semarang City. The implementation of good governance is the existence of services starting from the management of children's birth certificates, death certificates, Electronic ID cards, and various other public services that provide convenience for the people of Semarang. Intelligent people develop formal education in schools and universities that are evenly distributed to citizens based on IT, such as the implementation of e-learning, providing internet access as a source of information, and free schools for elementary and junior high school students. An innovative Economy is realized through increasing access, equity, relevance, and quality of essential social services, improving the quality and competitiveness of the workforce, controlling the number and rate of population growth, and increasing citizen participation.